Antibacterial Activity of Nanoemulsion Stem Fraction Pucuk Idat (Cratoxylum glaucum) - Yopan Pratama; Robby Gus Mahardika; Adisyahputra Adisyahputra (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
The idat plant is one of the endemic plants known to the people of bangka belitung  as well the shoot of idat (Cratoxylum glaucum). Cratoxylum glaucum is widely used as a traditional the skin, treat diarrhea, as antibacterial, anticancer,antivirus, and other diseases. Based on the potential of activity,the development of an Cratoxylum glaucum extract in the from of nanoemulsi is carried out which has stability and a small droplet size so that it isvery effective as an antibacterial. The purpose of this study was determine how the characterization and antibacterial activity of nanoemulsion from the Cratoxylum glaucum. Nanoemulsion was made using a homogenizer at a stirring speed of 8000 rpm for 30 minutes with a composition of 2,5 ml VCO, 10 ml tween 80, and 37,5 ml water. Nanoemulsion fraction MeOH : water from the shoot idat has a droplet size of 101,6 nm with a PI value of 0,274 and has a transmittance percent of 80,33% which can be categorized as a nanoemulsion with good stability compared to ethyl acetate and n-hexane nanoemulsion. In addition, nanoemulsion MeOH : water an antibacterial activity of S. Aureus by 10,42 cm which is categorized as strong.